If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.01(x + 5) + -0.05 = 0.01(6x + 5) Reorder the terms: 0.01(5 + x) + -0.05 = 0.01(6x + 5) (5 * 0.01 + x * 0.01) + -0.05 = 0.01(6x + 5) (0.05 + 0.01x) + -0.05 = 0.01(6x + 5) Reorder the terms: 0.05 + -0.05 + 0.01x = 0.01(6x + 5) Combine like terms: 0.05 + -0.05 = 0.00 0.00 + 0.01x = 0.01(6x + 5) 0.01x = 0.01(6x + 5) Reorder the terms: 0.01x = 0.01(5 + 6x) 0.01x = (5 * 0.01 + 6x * 0.01) 0.01x = (0.05 + 0.06x) Solving 0.01x = 0.05 + 0.06x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.06x' to each side of the equation. 0.01x + -0.06x = 0.05 + 0.06x + -0.06x Combine like terms: 0.01x + -0.06x = -0.05x -0.05x = 0.05 + 0.06x + -0.06x Combine like terms: 0.06x + -0.06x = 0.00 -0.05x = 0.05 + 0.00 -0.05x = 0.05 Divide each side by '-0.05'. x = -1 Simplifying x = -1
| 5.267-0.533=x | | 56x^2=16x | | 2.367-(1.45+1.45)=x | | 2.367+1.45+1.45=x | | 2.367+1.45=x | | 2.367+1.45= | | 0.01(x+5)-0.05=(6x+5) | | x-25=137 | | 6x+3(x-30)=63-x+3 | | 7x-9-10x-1= | | (2x-1)(x+2)=49 | | 9x-(5x+1)-[2+8x-(7x-5)]+9x=0 | | -3x-2/10=0.2x+4/3 | | 14*x^4+3x^2-28=0 | | 4-18=4x-6-3x | | 20x+3=-15 | | 4*0=x | | 3x-2y-(2x-3y)= | | 5(x+3)+2=5(x-8)-3x | | 3x+0-12=0 | | 3x^2+9x=6 | | 5(x-3)+2=5(x-8)-3x | | 54x^4-16x=0 | | -20x+10=-6-12x | | x=-6x^2-8x+10 | | y=-6x^2-8x+10 | | 2/3H-1/H+11=8 | | 8y-3=5y+3 | | 6x^2-2x=28 | | -x^2-6x-15=0 | | (24x-18)(4x+3)= | | 13+2(2x-2)=16-3x-7 |